Synthesis of 2,2-Dithiobisbenzamides Derivatives - Jhaumeer Laulloo, S. (Asian Journal of Chemistry, 2016)
2,2-Dithiosalicylic acid was converted into its pseudo amino acid via the formation of the anhydride followed by a Curtius rearrangement. An amino acid derived dithiolactam was also synthesized by coupling the corresponding bis-acid chloride with ethyl glycinate and subsequent Curtius rearrangement. A carboxy-protected pseudo amino acid was also prepared.